Lessons in innovation: how international news organisations combat disinformation through mission-driven journalism - Posetti, J; Simon, F; Shabbir, N (Reuters Institute for the Study of Journalism, 2019)
This report examines how digital-born news media in the Global South have developed innovative reporting and storytelling practices in response to growing disinformation problems. Based on field observation and interviews at Rappler in the Philippines, Daily Maverick in South Africa, and The Quint in India, we show that all three organisations combine a clear sense of mission and a commitment to core journalistic values with an active effort to find new ways of identifying and countering disinformation, based on a combination of investigative journalism fact-checking, data and social network analysis, and sometimes strategic collaboration with both audiences and platform companies. In the process, each of these organisations are developing new capacities and skills, sharing them across the newsroom, differentiating themselves from their competitors, and potentially increasing their long-term sustainability, in ways we believe other news media worldwide could learn from.